Analisis penanganan simpang 4 Kranggan, Cibubur, Jawa Barat - Doni Haidar Nur (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2020)
Cibubur is a buffer zone for Jakarta, which is the capital city of the Republic of Indonesia, which always increase in population and number of vehicles every year. This condition has led to an increase in traffic all networks in surrounding DKI Jakarta. Performance of traffic is measured by calculating the value of degree of saturation and delays at intersections. To measure the performance of the intersection, a standard that can be used as a reference in assessing traffic performance is required, and this study the standard is Indonesian Road Capacity Manual (MKJI) published by the Directorate General of Highways in 1997. Two calculation been held to indicate performance condition of traffic in Kranggan’s intersection. The first calculation is existing conditions or do nothing in this intersection and is got the service level of the Kranggan intersection is very bad (F) with a delay time of 83.05 seconds. Second calculation is condition with flyover or do something and the result is the service level of the Kranggan intersection is very good (A to B) with a delay time of 12.83 seconds.